Homestay Digital Marketing in Tourism Villages in South Sulawesi (Case Study in 3 Featured Tourism Village) - Daniel Adolf Ohyver; Hamsu Hanafi; Ali Muhtasom (PT. Publikasiku Academic Solution, 2023)
One type of accommodation that is widely found in tourist villages is homestay. Homestay is an accommodation that offers the experience of living together with locals in their homes. Homestay is a popular form of accommodation in tourist villages because it provides a different experience from other accommodations, as well as providing opportunities for tourists to interact with locals. Although homestays are in great demand by tourists, there are still some challenges in marketing them in tourist villages. One of the challenges faced by homestay marketers in tourist villages is the lack of knowledge on how to market effective homestays. In addition, homestays in tourist villages are also faced with competition with other accommodations such as hotels, villas, and other inns. The results showed that the homestay marketing strategy has not been effective enough in Tourism Villages in South Sulawesi, because homestay owners / managers and pokdarwis as homestay marketing coordinators in tourism villages have not had the right concept in their marketing. The role of information technology has not increased the effectiveness of homestay digital marketing in tourism villages in South Sulawesi due to limited digital literacy and resources.